2020
DOI: 10.3892/ijmm.2020.4499
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I induces apoptosis and protective autophagy in human glioblastoma cells via a reactive oxygen species‑dependent pathway

Abstract: Glioma is the most common primary malignancy of the central nervous system and is associated with high mortality rates. despite the available treatment options including surgery, radiotherapy and chemotherapy, the median patient survival rate is low. Therefore, the development of novel anticancer agents for the treatment of glioma is urgently required. Tanshinone I (TS I) is a tanshinone compound that is isolated from danshen. Accumulating evidence indicates that TS I exhibits antiproliferative activity in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Moreover, autophagy is reported to mediate nonapoptotic pathways via a tumor‐suppressive or oncogenic role. For example, the disruption of autophagy may promote tumorigenesis [17] and it could also be induced by anticancer cancer treatment [18,19]. Given this, investigating the regulatory role of apoptosis and autophagy appears to be particularly important for identifying valuable anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, autophagy is reported to mediate nonapoptotic pathways via a tumor‐suppressive or oncogenic role. For example, the disruption of autophagy may promote tumorigenesis [17] and it could also be induced by anticancer cancer treatment [18,19]. Given this, investigating the regulatory role of apoptosis and autophagy appears to be particularly important for identifying valuable anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy causes glioma cell death and sensitizes glioma cells for treatments involving chemotherapy and radiotherapy [ 20 , 21 , 32 ]. However, protective autophagy is an alternative mechanism for the glioma cells to avoid apoptosis [ 24 , 33 ]. The complicated actions of autophagy on glioma cell fate depend upon both the types of treatment and cellular dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that estrogen (ER) stress is closely related to cancer cell death and is an important downstream target of ROS. Guo’s group evaluated the anticancer potential of Tan I against glioblastoma and demonstrated that Tan I inhibited the proliferation of U87MG cells via the induction of apoptosis and G2/M cell cycle arrest ( Jian et al, 2020 ). Mechanistic experiments indicated that Tan I triggered ER oxidative stress and Akt-mediated apoptosis by inducing the accumulation of intracellular ROS.…”
Section: Targeting Autophagy For Human Cancersmentioning
confidence: 99%